Deficiencialismo: a invenção da deficiência pela normalidade - Souza, Renato Marcone José de [UNESP] (2015)
This thesis is divided into four parts. The first part consists of theorizing about the research question, inspired by readings of postcolonial theories, anti-colonial and literature review within the search area, Mathematics Education, Difference and Inclusion, culminating in the creation of a concept that will be used to analyze the data produced for this research. This concept, deficiencialism, appears in its embryonic form in this thesis, as it is still fragile, since it was not widely presented to the community and criticized in order to strengthen it. The second part of the thesis consists of three papers, one theoretical and two empirical. The theoretical article was written along with the supervisor of this research, which started a discussion on the concept of inclusion-exclusion, understanding that this is not fixed, rather is defined depending on the context. This discussion has contributed much to the development of the first part of the thesis. Then the empirical papers will use the first part of the thesis and this theoretical paper in their analysis. The third part deals with meta-search topics, ie they are answers to questions about an area of research. Two texts are in dialogue format with researchers Renato talked about this research and its relation to research and researchers who talk about social justice. The fourth part consists of final thoughts on the work, and a sketch of the notion of anti-deficiencialism and post-deficiencialism, naturally derived from the theory of the first concept also inspired by the post-colonial theories. Bring even in this part, the methodological research route in more detail